2011
DOI: 10.1016/j.bmcl.2011.07.100
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a new trifluoromethylketone analogue of l-arginine and contrasting inhibitory activity against human arginase I and histone deacetylase 8

Abstract: As part of our continuing search for new amino acid inhibitors of metalloenzymes, we now report the synthesis and biological evaluation of the trifluoromethylketone analogue of L-arginine, (S)-2-amino-8,8,8-trifluoro-7-oxo-octanoic acid (10). While this novel amino acid was initially designed as a potential inhibitor of human arginase I, it exhibits no measurable inhibitory activity against this enzyme. Surprisingly, however, 10 is a potent inhibitor of human histone deacetylase 8, with IC50 = 1.5 ± 0.2 μM. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…However, each compound differs in the nature of its head group designed to mimic substrate or tetrahedral transition state binding to the active site Zn 2+ ion. Most of these Zn 2+ -binding groups have been successfully incorporated into effective inhibitors of HDACs 29, 3339 and other metallohydrolases. 4043 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, each compound differs in the nature of its head group designed to mimic substrate or tetrahedral transition state binding to the active site Zn 2+ ion. Most of these Zn 2+ -binding groups have been successfully incorporated into effective inhibitors of HDACs 29, 3339 and other metallohydrolases. 4043 …”
Section: Resultsmentioning
confidence: 99%
“…For instance, inhibitors of the mammalian N 8 -acetylspermidine deacetylase have been described earlier, some of which exhibit low nanomolar inhibitory activity. 26, 27 So far, the HDAC inhibitor M344 28 and the trifluoromethylketone analogue of l -arginine 29 are the only compounds reported to inhibit the bacterial polyamine deacetylase in the low and mid-micromolar range, respectively. 18, 29 Here, we report the synthesis of new polyamine derivatives as well as new synthetic routes for some of the previously described mammalian N 8 -acetylspermidine deacetylase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two t-PFMKs showed potent inhibition (low-micromolar to sub-micromolar range) towards four HDAC isoforms [ 127 ]. Another example in this regard is represented by ( S )-2-amino-8,8,8-trifluoro-7-oxo-octanoic acid ( Figure 17 ), which is actually an l -Arg analogue initially designed by Ilies M. et al as a potential inhibitor of human arginase I that showed activity towards HDAC8 in the low-micromolar range (IC 50 = 1.5 μM) [ 128 ]. More recently (2018), Moreno-Yruele and Olsen C.A.…”
Section: Peptidyl Tri-fluoromethyl Ketones (T-pfmks)mentioning
confidence: 99%
“…4 Due to their role in various biological functions, HDAC inhibition has become a promising epigenetic target for the treatment of cancer. 5 HDAC inhibitors (HDACis) are structurally diverse and are classified into various groups as hydroximates, [6][7][8] cyclic tetrapeptides, 9 benzamides, 10,11 electrophilic ketones, 12 and carboxylic acids. 13 Two HDACis (vorinostat and romidepsin) have been approved by the United States Food and Drug Administration for the treatment of cutaneous T-cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%